Universal Stress Proteins Contribute Edwardsiella ictaluri Virulence in Catfish - Akgul, Ali; Nho, Seong Won; Kalindamar, Safak; Tekedar, Hasan C.; Abdalhamed, Hossam; Lawrence, Mark L.; Karsi, Attila (Frontiers in Microbiology, 2018)
Edwardsiella ictaluri is an intracellular Gram-negative facultative pathogen causing enteric septicemia of catfish (ESC), a common disease resulting in substantial economic losses in the U.S. catfish industry. Previously, we demonstrated that several universal stress proteins (USPs) are highly expressed under in-vitro and in-vivo stress conditions, indicating their importance for E. ictaluri survival. However, the roles of these USPs in E. ictaluri virulence is not known yet. In this work, 10 usp genes of E. ictaluri were in-frame deleted and characterized in vitro and in vivo. Results show that all USP mutants were sensitive to acidic condition (pH 5.5), and Ei∆usp05 and Ei∆usp08 were very sensitive to oxidative stress (0.1% H2O2). Virulence studies indicated that Ei∆usp05, Ei∆usp07, Ei∆usp08, Ei∆usp09, Ei∆usp10, and Ei∆usp13 were attenuated significantly compared to E. ictaluri wild-type (EiWT) (20%, 45%, 20%, 20%, 55%, 10% vs. 74.1% mortality, respectively). Efficacy experiments showed that vaccination of catfish fingerlings with Ei∆usp05, Ei∆usp07, Ei∆usp08, Ei∆usp09, Ei∆usp10, and Ei∆usp13 provided complete protection against EiWT compared to sham-vaccinated fish (0% vs. 58.33 % mortality). Our results support that USPs contribute E. ictaluri virulence in catfish.